Swelling-resistant graphene oxide membranes reinforced by heteroatomic inorganic dots for electrochemical lithium recovery from aqueous solution - Kim, Tae Nam; Kim, Hyunjin; Kim, Choonsoo; Hwang, Jongkook (Desalination, 2024)
Graphene oxide (GO)-based membranes (GOMs) hold great promise for electrochemical Li+ separation due to their exceptional water permeability and ion selectivity. However, their application is limited by the interlayer swelling and poor stability in aqueous solutions. Here we report a heteroatomic sol-reinforcing dot (HARD) strategy using aluminosilicate (AS) sols as physical crosslinkers. Subnanometer-sized AS sols are inserted into GO interlayers to create percolated AS gel networks that improve the swelling resistance and hydration stability. AS sols neutralize/stabilize the negatively charged GO interlayers with tunable positive charges from Si-O-Al motifs, allowing precise tuning of interlayer spacing. The fabricated AS/GOMs show remarkably enhanced stability and lithium-ion selectivity over various metal ions (Ni2+, Co2+, Mn2+, and Fe3+) compared to unmodified GOM under H-type cell experiments. Furthermore, the optimal AS/GOM is applied to a continuous redox-mediated electrodialysis system, achieving a record-high Li+ permeation of 2.0 mol m−2 h−1 and Li+/Fe3+ selectivity of 42. Considering a variety of heteroatom combinations and the ease of sol-gel processing, this approach allows the development of robust GOMs for diverse separation applications.
Keywords: Electrochemicals; Fe 3+; Graphene oxide membrane; Graphene oxides; Heteroatomic sol; Ion selectivity; Li +; Lithium recoveries; Oxide membrane; Sol-gel chemistry; Graphene oxide membrane; Heteroatomic sol; Lithium recovery; Redox reaction; Sol-gel chemistry